A Case Study Using a Behavioural Contract in Alcohol Dependence within a Crisis Home Treatment Team - Howe, Andrew John; Anandarajah, Cholan (Case Reports in Psychiatry, 2022)
In this case study, we present a novel approach to care within a Home Treatment Team, using a behavioural contract. This is a signed, written agreement that targets specific behaviours for change. The concept draws on social learning theory in that it requires social interaction and a relationship to work. In psychiatric settings, the behavioural contract often finds use in Democratic Therapeutic Communities but rarely in crisis or acute services. In this case study, we attempted to use a behavioural contract within our Home Treatment Team to help a patient address his alcohol dependence and its subsequent effect on his daily living activities. The behavioural contract provided an alternative way to manage a crisis episode. We hope that other crisis service staff reading this case study may use a behavioural contract in their work to a similar beneficial effect.